Deciphering the Layers of Myth : Devdutt Pattanaik’s Interpretative Approach to Mythology as a Bridge Between Ancient Wisdom and Contemporary Thought - Rashmi; Dr. Sushil Kansal (International Journal of Scientific Research in Humanities and Social Sciences, 2025)
Mythology serves as an essential framework for understanding cultural identity, ethics, and human behavior. Devdutt Pattanaik’s interpretative approach positions mythology as a dynamic and evolving tradition rather than a set of fixed historical narratives. His extensive analysis draws from diverse sources, including Vedic literature, Puranic texts, folk traditions, and global mythological systems, to present mythology as a fluid construct that adapts to the needs of changing societies. His work challenges singular and dogmatic readings of myths by emphasizing their multiple perspectives, symbolic depth, and socio-cultural significance. Through his exploration of ancient stories, he underscores their relevance in shaping contemporary thought, governance, and ethical dilemmas. A significant contribution of Pattanaik’s work is his comparative analysis of Eastern and Western mythological traditions. He contrasts the cyclical and pluralistic nature of Indian mythology with the linear and often monotheistic structure of Western mythologies, demonstrating how these frameworks influence cultural attitudes toward power, morality, and destiny. Indian myths, according to Pattanaik, are built upon coexisting truths, multiple interpretations, and layered narratives, while Western myths tend to follow a hero-centric progression of good versus evil. His analysis highlights the philosophical and ethical flexibility in Indian mythology, showing that mythological narratives are not rigid doctrines but evolving reflections of societal consciousness. Another key aspect of Pattanaik’s interpretative methodology is his engagement with psychology and symbolic representation in myths. He integrates Carl Jung’s archetypal theory and Joseph Campbell’s monomyth framework to analyze how mythological figures function as psychological models for human behavior. His work explores how deities, heroes, and epic figures embody human traits, dilemmas, and aspirations, offering a metaphorical map of human emotions and ethical struggles. By decoding symbols, rituals, and divine iconography, he reveals how mythology serves as a guide for self-awareness, leadership, and social values. His interpretations focus on cultural conditioning, behavioural psychology, and the subconscious impact of myths, presenting mythology as a tool for understanding both individual growth and collective identity formation. Pattanaik also extends his mythological studies into contemporary socio-political and organizational structures. His insights into mythology’s application in business ethics, leadership models, and governance systems present an alternative approach to management and decision-making. By drawing from Indian mythological traditions, he critiques Western capitalist models of leadership that prioritize hierarchy and authority, advocating instead for decentralized, inclusive, and value-driven leadership inspired by Indian epics. His approach suggests that mythology can offer wisdom not just in religious or literary contexts but also in modern economic, corporate, and administrative spheres. Gender representation is another critical theme in Pattanaik’s mythological interpretations. He examines how myths have been historically used to construct and reinforce gender roles, particularly in the context of power, morality, and societal expectations. His analysis of feminine and masculine archetypes in mythology highlights how gender narratives have evolved and continue to shape contemporary discourses on equality, agency, and identity. He deconstructs stereotypical representations of women in mythology, offering alternative perspectives that challenge patriarchal readings of ancient texts. His work contributes to the broader conversation on gender politics, intersectionality, and the reinterpretation of traditional roles in contemporary society. Pattanaik’s interpretative style is notable for its accessibility and multidisciplinary engagement. He integrates historical inquiry, religious studies, cultural anthropology, and modern philosophy to make mythology relevant to diverse audiences. His emphasis on visual storytelling, cross-cultural references, and practical applications ensures that mythology is not confined to academic discourse but remains an integral part of contemporary cultural and intellectual engagement. He encourages a non-dogmatic, open-ended approach to myths, urging readers to interpret mythology as a framework for critical thinking rather than a rigid belief system. Pattanaik’s mythological interpretations redefine the study of ancient narratives by making them relevant in contemporary contexts. His approach highlights the adaptability, plurality, and symbolic richness of mythology, demonstrating how these narratives continue to shape human civilization. By deconstructing rigid structures, engaging with psychology, and exploring mythology’s application in leadership and ethics, Pattanaik transforms mythology into a living discourse that bridges past wisdom with modern realities. His contribution lies not only in preserving myths but also in repositioning them as tools for understanding contemporary life, cultural evolution, and philosophical inquiry.